Topografia Applicata al Soccorso: la formazione del Vigile del Fuoco - Mercuri, Daniele (GEOmedia, 2022)
The Italian T.A.S. (Applied Topography to Rescue Service) supports the activities of the National Fire Brigade with the use of advanced geographical information referring to the emergency scenario and, in particular, to the scenarios that require the intervention of the National System of civil protection. The training focuses on the knowledge of the concept of coordinates which then allows to deal with the use of topographic maps and subsequently that of the GNSS system. A theoreticalpractical course structured on interventional reality and aimed at making the learner understand the importance of this knowledge for technical rescue and for the safety of the operator himself.